RASIONALITAS KONSEPSI BUDAYA NUSANTARA DALAM MENGGAGAS PENDIDIKAN KARAKTER BANGSA MULTIKULTURAL - Muali, Chusnul (JURNAL ISLAM NUSANTARA, 2017)
Culture is a value, norm, morals and beliefs, assumptions that are believed by the commodities of society. A culture that expresses a person's behavior is distorted, right, wrong, or good. As social beings, human beings give birth to systems of thinking, values, norms, rules and beliefs. However, humans also become part of what it produces. When human life moves with its dynamics, the dynamically moving is the systematic it has produced. Cultural education is done through the education of values or virtues that become the basic values of the nation's culture. The virtue that attributes culture is essentially value. Therefore, cultural education is basically the development of values derived from the perspective of life or ideology of the Indonesian nation, religion, culture, and values formulated in the goals of national education.